Kompoziti iz skorje: nova gozdarsko-lesarska vrednostna veriga - Medved, Sergej (Gozdarski vestnik, 2023)
Bark is a multifunctional material because it acts as a protection (against physical and mechanical damage, as well as against biological degradation), allows transport of water and gases, occasionally helps with photosynthesis, and provides support to the tree. Bark represents between 10% and 20% of the total tree mass, but a significant proportion of the bark remains unused. With the aim of demonstrating the potential use of bark to produce various composites, we produced and analysed three different composites: wood-plastic composite made of bark and polyethylene, three-layer panel composite made of bark bonded with melamine-urea-formaldehyde adhesive and single-layer panel composite made of wet bark chips bonded with tannin adhesives.
Keywords: bark; iveri; iverna plošča; lesno plastični kompozit; particleboard; particles; skorja; wood plastic composite